120k views
0 votes
Given the algebraic expression 125x7^3) -1^3 create an equivalent expression.​

Given the algebraic expression 125x7^3) -1^3 create an equivalent expression.​-example-1
User SergioFC
by
4.9k points

1 Answer

5 votes

Answer:

third option

Explanation:

using the rule of exponents


(a^m)^(n) =
a^(mn)


a^(-m) =
(1)/(a^(m) )


a^{(m)/(n) } =
(\sqrt[n]{a})^m

given


(125x^{(7)/(3) }) ^{-(1)/(3) }

=
125^{-(1)/(3) } ×
x^{-(7)/(9) }

=
\frac{1}{125^{(1)/(3) } } ×
\frac{1}{x^{(7)/(9) } }

=
\frac{1}{\sqrt[3]{125} } ×
\frac{1}{x^{(7)/(9) } }

=
(1)/(5) ×
\frac{1}{x^{(7)/(9) } }

=
\frac{1}{5x^{(7)/(9) } }

User Robertjmoore
by
5.7k points